Therapeutic Effect of C-Vx Substance in K18-hACE2 Transgenic Mice Infected with SARS-CoV-2 - Polat, Hivda Ulbegi; Abaci, Irem; Tas Ekiz, Arzu; Aksoy, Ozge; Oktelik, Fatma Betul; Yilmaz, Vuslat; Tekin, Saban; Okyar, Alper; Oncul, Oral; Deniz, Gunnur (MDPI, 2023)
C-Vx is a bioprotective product designed to boost the immune system. This study aimed to determine the antiviral activity of the C-Vx substance against SARS-CoV-2 infection. The effect of C-Vx in K18-hACE2 transgenic mice against the SARS-CoV-2 virus was investigated. For this purpose, ten mice were separated into experimental and control groups. Animals were infected with SARS-CoV-2 prior to the administration of the product to determine whether the product has a therapeutic effect similar to that demonstrated in previous human studies, at a histopathological and molecular level. C-Vx-treated mice survived the challenge, whereas the control mice became ill and/or died. The cytokine-chemokine panel with blood samples taken during the critical days of the disease revealed detailed immune responses. Our findings showed that C-Vx presented 90% protection against the SARS-CoV-2 virus-infected mice. The challenge results and cytokine responses of K18-hACE2 transgenic mice matched previous scientific studies, demonstrating the C-Vx's antiviral efficiency.
Keywords: C-Vx; SARS-CoV-2; COVID-19; antiviral; cytokines; neutralization; Biochemistry & Molecular Biology; Chemistry